PENDAMPINGAN STRATEGI PENJUALAN DAN PELAYANAN KONSUMEN BAGI DRIVER FORESTEA DI BANDAR LAMPUNG - Armunanto, Yohanes Novi; Qurrota Ayu Nindien; Nadya Ramadhani Ikhsana (BEGAWI : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve sales strategies and consumer service skills of Forestea drivers in Bandar Lampung. Forestea is a beverage MSME that applies a mobile selling concept using electric bicycles; however, it still faces challenges related to personal selling skills, marketing communication, and service consistency. The method applied in this program was participatory mentoring combined with applicative training, including field observation, discussions, material delivery, sales simulations (role play), and direct assistance during field implementation. The activity was conducted at the Forestea warehouse located at Jl. P. Senopati 1C, Jatimulyo, Jati Agung, South Lampung. The results indicate an improvement in drivers’ understanding and skills in persuasive communication, personal selling techniques, and professional consumer service. Drivers demonstrated higher confidence in offering products and interacting with customers, which potentially enhances customer satisfaction and sales performance. This activity confirms that practical and needs-based mentoring is effective in strengthening MSME human resource competencies and supporting business sustainability.